Clinical and Genetic Study on a Chinese Patient with Infantile Onset Epileptic Encephalopathy carrying a PPP3CA Null Variant: a case report - Sai Yang; Xiang Shen; Qingyun Kang; Xiaojun Kuang; Zeshu Ning; Shulei Liu; Hongmei Liao; Zhenhua Cao; Liming Yang (BMC, 2020)
Abstract Background PPP3CA gene encodes the catalytic subunit A of a calcium-dependent protein phosphatase called calcineurin. However, two distinct mechanisms in PPP3CA deficiency would cause two clinically different diseases. Gain-of-function mutations in the autoinhibitory domain at the C-terminus would cause ACCIID that stands for arthrogryposis, cleft palate, craniosynostosis and impaired intellectual development. While loss-of-function mutations in PPP3CA would cause infantile or early childhood onset epileptic encephalopathy1, named as IECEE1. IECEE1 is a severe epileptic neurodevelopmental disorder and mainly characterized by psychomotor delay. Here, we report a Chinese patient who was clinically and genetically diagnosed as IECEE1. We also extensively analyzed electroencephalogram (EEG) features of the patient in this study. Case presentation A 2-year-old Chinese patient who had recurrent polymorphic seizures was clinically and genetically diagnosed as IECEE1. A frameshift variant c.1283insC (p.T429NfsX22) was identified in this case. Multiple types of abnormal features were observed in the EEG, comparing with the previous reports. Conclusions These findings could expand the spectrum of PPP3CA mutations and might also support the diagnosis and further study of IECEE1.